Monocyte Lymphocyte Ratio, Platelet Lymphocyte Ratio, Neutrophil Lymphocyte Ratio as Prognostic Markers in Patients with Multidrugs Resistant Tuberculosis Treated at Ulin General Hospital Banjarmasin - Bagus Wicaksono (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Multi Drugs Resistant Tuberculosis (MDR TB) is tubercolusis with the least resistance to rifampicin and isoniazid. The progresivity and side effects of MDR TB treatment can be monitored through clinical, imaging, and laboratory evaluation. Monocyte Lymphocyte Ratio (MLR), Neutrophil Lymphocyte Ratio (NLR), and Platelet Lymphocyte Ratio (PLR) are the inflammatory markers used as biomarkers of treatment progress in MDR TB. The purpose of this research was to determine the difference of MLR, NLR, and PLR value pre and post MDR TB therapy and to determine the best prognostic biomarker in the evaluation of MDR TB treatment progress at Ulin General Hospital in January-December 2017. This research was an analytic observational study with a cross-sectional design. The sample was 17 patients selected based on the inclusion and exclusion criteria. Results obtained from paired T-tests showed the decreasing of MLR, NLR, PLR value in MDR TB patients receiving TB therapy. PLR had a more role as inflammatory biomarker of MDR TB treatment with p = 0.000, compared to MLR (ρ = 0.01), and NLR ( ρ = 0.006). The conclusion is PLR was significantly the best prognostic biomarker for MDR TB treatment. Keywords: MDR TB, Monocyte Lymphocyte Ratio, Neutrophil Lymphocyte Ratio, Platelet Lymphocyte Ratio